Organic fertilizer comparison on kale (Brassica spp.) varietal growth and nutrient content - Yoder, Natalie, author; Davis, Jessica, advisor; Stonaker, Frank, committee member; Elliott, Adriane, committee member (Colorado State University. Libraries, 2014)
Selecting supplemental N fertilizer for use on certified organic farms can be difficult and confusing. There are many options commercially available to farmers with similar N concentrations but widely different ingredients. Field experiments on three farms in Fort Collins, CO were conducted to evaluate the impact of a few commonly-used organic fertilizers on kale yield and nutrient concentrations. This study includes a fertilizer under development which is produced on-farm utilizing N-fixing cyanobacteria; this cyanobacterial bio-fertilizer may be a viable choice for farmers in the near future. The three fertilizer treatments (hydrolyzed fish, alfalfa meal and liquid cyanobacteria) were applied at rates calculated by subtracting soil nitrate-N concentration from a target 50 mg/kg. Cyanobacteria and hydrolyzed fish were applied in liquid form while alfalfa was incorporated dry into the soil pre-planting. Biweekly measurements of plant height and chlorophyll content were taken on three varieties of kale, Dinosaur, Red Russian, and Winterbor. Leaf weight, leaf area, N, Fe and Zn concentrations were measured during four monthly harvests. Organized in a split-plot experimental design, each farm had 3 treatment replications with subplots of different kale varieties. No significant effects were found on plant height, leaf weight, leaf area, N, Fe or Zn concentrations among fertilizer types. There were varietal differences in plant height, leaf area, and general performance as well as resistance to pest pressure. Residual N in each subplot was measured after this study and showed significant difference among varieties. Kale variety choice seems to have a much larger impact on yield and nutrient concentrations than fertilizer choice, as long as fertilizers are applied at similar N rates.
Keywords: cyanobacteria; fertilizer; kale; organic; variety; vegetable